Use of Metacognition Questions, Hands-On Activity, and Fantasy Ironwood Tree Metaphor for Trigonometry Learning - Demitra, Demitra; Dewi, Ummi Fortuna (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
The challenge of mathematics teacher of SMAN-2 Palangka Raya was student boredom.Ã‚Â The aim of research (1) increases the studentsÃ¢â‚¬â„¢ enthusiasm in learn trigonometry and (2) increase the learning outcome of multiplication to addition and subtraction identity of sine and cosine, used metacognition questions and fantasy ironwood tree metaphor integrated to hands-on activity. The research used the classroom action research method in three cycles of action. The subjects were 40 students of grade XI MIPA4 Specialization SMAN-2 Palangka Raya. Data comprised of learning journal, photos and video recording, and studentsÃ¢â‚¬â„¢ answer, collected through observation and interview, and analyzed through reduction and tabulation. The research result showed the classroom atmosphere change as the impact of action implementation, in which (1) the increase of right answers numbers; (2) the emerge of learning enthusiasm; (3) the variation product of the fantasy ironwood tree creation.Tantangan guru matematika SMAN-2 Palangka Raya munculnya kebosanan. Tujuan penelitian untukÃ‚Â (1) meningkatkan semangat siswa belajarÃ‚Â trigonometri, (2) meningkatkan hasil belajar identitas perkalian ke penjumlahan dan pengurangan sine dan cosine, melalui penggunaan pertanyaan metakognisi dan metafora pohon ulin fantasi yang diintegrasikan dalam hands-on activity. Penelitian dilakisanakan dengan metode penelitian tindakan kelas dengan tiga siklus tindakan. Subjek penelitian 40 siswa kelas XI MIPA 4 Peminatan SMAN-2 Palangka Raya. Data berupa jurnal mengajar, rekaman foto-foto dan video, serta jawaban siswa, dikumpulkan dengan pengamatan dan wawancara yang dianalisis melalui reduksi dan tabulasi.Ã‚Â Hasil penelitian menunjukkan perubahan suasana kelas sebagai dampak pelaksanaan tindakan, dimanaÃ‚Â (1) terjadi peningkatan jumlah jawaban benar; (2) teramati munculnya semangat belajar ; (3)Ã‚Â produk kreativitasÃ‚Â pohon ulin fantasi yang beragam dengan tempelan jawaban soal-soal identitas perkalian sinus dan cosinus.Ã‚Â